Recomendaciones de Liderazgo para los Dueños de Pymes Familiares Exportadoras y no Exportadoras en Nuevo León (Leadership recommendations for exporting and nonexporting family SME´s owners in Nuevo Leon) - Treviño Ayala, María Eloísa; Villalpando Cadena, Paula; Lozano Treviño, David Fernando; Barragán Codina, José Nicolás (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract: The main purpose of this document is to state the importance that small and medium-sized enterprises (SMEs) exporting and non-exporting have, as well as family businesses in Mexico´s economy and specifically in the state of Nuevo Leon. It establishes certain family SMEs, exporting and non-exporting, characteristics to take into consideration by Nuevo Leon leaders that seek success under the determinant of profits. It also locates qualities, from our stand point, classic and contemporaries, recommended for managers and administrators of this type of companies.